Война языков или культурная оппозиция на примере Black English и социолекта военных США - Харченко, О.В. (Культура народов Причерноморья, 2002)
The article “ The War of Languages or Cultural Opposition on the Example of Black English and the
Sociolect of Military Servicemen” deals with the problem of bilingual antonymous words and cultural
opposition. It gives examples of antonymous homonyms, which exist on the level of one language (Black
English against General American, and Military sociolect against General American). The author singles out the
following types of cultural opposition: ethnic cultural opposition, social cultural opposition, national cultural
opposition. The main task of cultural opposition is to create the negative ethnic, national or social stereotype.